HAK ASASI MANUSIA DALAM PERSPEKTIFFILSAFAT HUKUM - Reko Dwi Salfutra (PROGRESIF: Jurnal Hukum, 2018)
Human Rights is a moral principle and its justification is in the philosophical moral.Understanding of human rights in the perspective of philosophical morality is believed to find the correct or at least deepening arguments for understanding the truth of human rights.Pancasila as the ideology of the Indonesian contains the idea that humans are created by God by carrying out two aspects, namely aspects of individuality and aspects of sociality. Therefore, everyone’s freedom is limited by the rights of others. This means that everyone has the obligation to recognize and respect the human rights of others.